Effective Coating Barriers for Protection of Reinforced Concrete (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
Effective coating barriers could provide protection to reinforced concrete, helping it to withstand the effects of harmful substances. Effective coating barriers include coatings on concrete surfaces and steel surfaces. Coatings on concrete surfaces can include silane and other waterproof materials that prevent the ingress of water. Coatings on steel surface can include epoxy, which isolates the steel from harmful substances. Other innovative coatings can also be applied. There is an urgent need to understand the performance of these coatings, especially their long-term performance, including in terms of bonding loss, degradation, etc. Topics of interest for this Special Issue include, but are not limited to, the following: The long-term performance of coatings on steel or concrete surfaces in reinforced concrete; The degradation mechanisms of coatings; Epoxy coatings on steel in concrete; Silane coatings on concrete surfaces; Innovative coatings on concrete surfaces, such as waterproof coatings, breathable coatings, etc.